Answer:
the answer is x=2
Step-by-step explanation
First of all put all x in one side of equation and number to the other side
Bare in mind that when we move from one side of equation to another positive integers become negative and negative integers become positive
5x-6=2x
5x-2x=6 here we moved 2x to other side of equation thus, it become -2x, and -6 was moved to other side of equation thus it become 6
3x=6 we subtracted from 5x-2x and found 3x since we can subtract the variables having the same element i this case that is x
x=6/3 we divided 6/3 in order to find the value of x. please note that 3x means 3*x
x=2